Environmental Concern, Subjective Norm, Eco Labels, and Green Purchase Intention: The Moderating Role of Social Media Information in the FMCG Industry - Meisa; Giriati; Erna Listiana; Nur Afifah; Ana Fitriana (Al-Qalam Institue, 2026)
Plastic pollution has become a global environmental issue with serious ecological consequences. Reports from the United Nations Environment Programme indicate that global plastic waste production exceeds 400 million tons annually, with a significant portion originating from packaging waste generated by the Fast-Moving Consumer Goods (FMCG) industry. This study aims to analyze the influence of Environmental Concern (EC), Subjective Norm (SN), and Eco Labels (EL) on Green Purchase Intention (GPI), while also examining the moderating role of Social Media Information (SMI). The research employed a quantitative approach using a survey of 210 consumers selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 at a 5% significance level. The results reveal that Environmental Concern, Subjective Norm, Eco Labels, and Social Media Information have a positive and significant effect on Green Purchase Intention. Furthermore, Social Media Information does not moderate the relationship between Environmental Concern and Green Purchase Intention, but it significantly moderates the relationship between Subjective Norm and Green Purchase Intention. These findings provide empirical contributions to the literature on green consumer behavior and offer practical implications for strengthening sustainable marketing strategies and environmental communication in the FMCG sector.